STUDY OF ADMINISTRATIVE AND CULTURAL DEVELOPMENTS IN THE ERA OF BADAMI CHALUAKYAS - Muniraju M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Badami Chalukyas (543–757 CE) were instrumental in shaping the socio-political and cultural landscape of southern India. Through effective governance, military conquests, and cultural patronage, they established a stable and prosperous empire in the Deccan region. This study presents an extensive analysis of their administrative framework, legal system, revenue collection, military strategies, and contributions to art, architecture, and literature. In addition, it examines the broader cultural context, particularly religious and philosophical developments that flourished during this period. By incorporating primary inscriptions, epigraphical data, and contemporary scholarly work, this research aims to offer an original and comprehensive understanding of the era’s political, social, and cultural achievements.